Pengaruh Kartu Disiplin Siswa Terhadap Hasil Belajar PKn Kelas VI di SD Negeri 79 Palembang - Muslimah, Erda; Syaflin, Sylvia Lara; Akbar, M. Taheri (Indonesian Research Journal on Education, 2022)
Character education according to Magawangi in Kusuma (2013: 5) character education is an effort to educate children so that they can make wise decisions and practice them in everyday life, so that they can make a positive contribution to their environment. character education is an effort to educate children to make decisions in everyday life so that they can make a positive contribution to their environment. Based on these observations, SD Negeri 79 Palembang already has character education there, but one of thecharacter educations that has not been sufficiently fulfilled is the character of discipline. To determine the development of student discipline levels, researchers used student discipline cards. This study aims to determine whether there is an effect of student discipline cards on the learning outcomes of Civics ingrade IV SD Negeri 79 Palembang. This research is an experimental research type with quantitative data analysis. This study uses a quasi-experimental research method (quasi-experimental) design in this study posttest only control design. The population in this study were all students of class IV Negeri 79 Palembang. The sampling technique using simple random sampling technique, obtained two classes assamples, namely class IV.A as the experimental class and IV.B as the control class. The instrument used is the Civics learning outcome test for student discipline material. Testing the data hypothesis in this study was using the independent sample t-test. The average posttest result for the experimental class was 86.5%, the control class was 68%. Based on Mann Whitney's t-test calculation, asymp.sig (2-tailed) is .000 < 0.05 indicating there is a significant difference between the learning outcomes of the two classes.